Communication Modeling Approaches in Energy System Applications: A Systematic Overview - Malin Radtke; Emilie Frost; Astrid Niebe; Sebastian Lehnhoff (IEEE Access)
The integration and consideration of communication networks in energy system studies is of critical importance due to the mutual dependencies that exist between the systems. These interdependencies have an impact on the overall performance, stability, and robustness of the energy system. There is no comprehensive guide or overview for integrating communication into power system applications, despite its recognized importance and the wide variety of existing solutions that take into account interdependencies. By providing a detailed overview, characterization, and classification of existing approaches to communication modeling, this paper contributes to filling this gap in existing guidelines or general descriptions for the integration of communication in power system applications. In addition to discussing the multiple objectives associated with different focus for modeling communication, we consider the required data and system perspectives. Therefore, this paper provides guidance on the selection of a suitable and applicable communication modeling approach, given the specific objective and prerequisite.